A meta-analysis of randomized controlled trials: Efficacy of selenium treatment for sepsis. Issue 9 (March 2019) - Li, Shaojun; Tang, Tian; Guo, Pengfei; Zou, Qing; Ao, Xiaoxiao; Hu, Lan; Tan, Liping
Abstract: Background: To understand the clinical outcomes of selenium therapy in patients with sepsis syndrome, we conducted a meta-analysis of randomized controlled trials (RCT). Methods: A total of 13 RCTs comparing selenium and placebo for patients with sepsis were reviewed systematically. Results: However, we could not detect the association of selenium treatment with a decreased mortality at different time course (relative risk [RR] [95% confidence interval, CI]: 0.94 [0.82–1.06] at day 28; 0.73 [0.36–1.47] at day 90; 1.16 [0.78–1.71] at 6 months; respectively). Selenium supplementation did not show favorable efficacy in the incidence of renal failure, secondary infection or duration of mechanical ventilation (RR [95% CI]: 0.65 [0.41–1.03]; 0.96 [0.87–1.06]; standard mean difference [SMD] [95% CI]: 0.17 [−0.30–0.63]; respectively). Interestingly, we found that selenium therapy was benefit for sepsis patients with reduced duration of vasopressor therapy, staying time in intensive care unit and hospital, and incidence of ventilator-associated pneumonia (SMD [95% CI]: −0.75 [−1.37 to −0.13]; −0.15 [CI: −0.25 to −0.04]; −1.22 [−2.44 to −0.01]; RR [95% CI]: 0.61 [0.42–0.89]; respectively). Conclusion: Based on our findings, intravenous selenium supplementation could not be suggested for routine use. Abstract : Supplemental Digital Content is available in the text